2009
DOI: 10.3819/ccbr.2009.40009
|View full text |Cite
|
Sign up to set email alerts
|

Elephant cognition in primate perspective

Abstract: On many of the staple measures of comparative psychology, elephants show no obvious differences from other mammals, such as primates: discrimination learning, memory, spontaneous tool use, etc. However, a range of more naturalistic measures have recently suggested that elephant cognition may be rather different. Wild elephants sub-categorize humans into groups, independently making this classification on the basis of scent or colour. In number discrimination, elephants show no effects of absolute magnitude or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 119 publications
1
44
0
1
Order By: Relevance
“…Past research on the African elephants' visual system states that they can detect important conspecific behavioral cues, such as ear and trunk movements (Byrne et al, 2009;Kahl & Armstrong, 2000) as well as important heterospecific behavioral cues, such as human pointing, face and body orientation (Smet & Byrne, 2013; however, research by Plotnik et al (2013) found that Asian elephants could not follow human pointing cues. The results of the current study suggest that Asian elephants are able to detect more subtle visual cues, which may be important for establishing and maintaining social bonds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research on the African elephants' visual system states that they can detect important conspecific behavioral cues, such as ear and trunk movements (Byrne et al, 2009;Kahl & Armstrong, 2000) as well as important heterospecific behavioral cues, such as human pointing, face and body orientation (Smet & Byrne, 2013; however, research by Plotnik et al (2013) found that Asian elephants could not follow human pointing cues. The results of the current study suggest that Asian elephants are able to detect more subtle visual cues, which may be important for establishing and maintaining social bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Asian elephants have large brains (Hart, Hart, McCoy, & Sarath, 2001), with an encephalization quotient similar to that of apes (Byrne et al, 2009;Eisenberg, 1981). They also possess a similar number of cortical neurons as humans.…”
mentioning
confidence: 99%
“…Humans, chimpanzees (Whiten et al, 2001), orangutans (van Schaik et al, 2003), gorillas (Breuer, NdoundouHockemba, & Fishlock, 2005), capuchin monkeys (Ottoni, Dogo de Resende, & Izar, 2005), bottlenose dolphins (Krutzen, Mann, Heithaus, Connor, Bejder, & Sherwin, 2005), elephants (Byrne, Bates, & Moss, 2009), crows (Hunt & Grey, 2003 and Wnches (Tebbich & Bshary, 2004) exhibit tool improvisation in the wild. The most familiar tools of any animal are its own limbs, and the most fundamental cases of tool improvisation involve using an object common to the animal's environment to augment the reach or force of an animal's limbs.…”
Section: Structure Mapping In Tool Improvisationmentioning
confidence: 97%
“…Bottlenose dolphins adapt sponges as head-mounted Wshing tools (Krutzen et al, 2005;Mann et al, 2008). Elephants manufacture and employ tools for personal hygiene (Byrne et al, 2009). Capuchin monkeys use stones to crack nuts (Ottoni et al, 2005;Visalberghi, Fragaszy, Ottoni, Izar, de Olviera, & Andrade, 2007).…”
Section: Structure Mapping In Tool Improvisationmentioning
confidence: 99%
“…But data mining can be used deliberately to suggest and ground innovative experimentation. Elephants have a popular reputation for intelligence but until recently, experimental studies provided far from inspirational results, implying that elephants were slow to learn and lacked even the basic components of social knowledge [12]. Data mining of the long-running study at Amboseli suggested the possibility that wild elephants might have more powerful cognitive abilities, which led to a series of novel field experiments and some quite surprising results.…”
mentioning
confidence: 99%